Diversidade genética e adaptabilidade de monosporascus e macrophomina isolados de plantas daninhas em áreas de cucurbitáceasDiversidade genética e adaptabilidade de monosporascus e macrophomina isolados de plantas daninhas em áreas de cucurbitáceas - Negreiros, Andréia Mitsa Paiva (Universidade Federal Rural do Semi-Árido, 2019)
Brazil is the world's largest producer of tropical fruits, highlighting melon and watermelon. Umpteen problems are caused by root pathogens in both cultures. Among them we highlight fungi of the genera Monosporascus and Macrophomina. Weeds present in the cultivated areas can act as alternative hosts of these soilborne fungi. Therefore, the objective of this work was to know the genetic diversity and adaptability of Monosporascus and Macrophomina isolated from weeds in melon production fields in Northeastern Brazil. In the first work, a collection of 35 isolates of Monosporascus spp. from roots of two weed species prevalent in cucurbits fields of cultivation in Northeastern Brazil, Trianthema portulacastrum and Boerhavia diffusa, were used in this study. These isolates were identified based on DNA sequences of Internal Transcribed Spacer regions (ITS) of the nuclear rDNA, part of the translation elongation factor gene (tef-1α), part of the β-tubulin gene (tub), part of the nuclear small subunit rDNA (SSU), and part of the large subunit rDNA (LSU). Five new species of Monosporascus were identified worldwide, being M. brasiliensis, M. caatinguensis, M. mossoroensis, M. nordestinus and M. semiaridus. Monosporascus brasiliensis, M. nordestinus and M. semiaridus were isolated from both weed species, while M. caatinguensis only from T. portulacastrum and M. mossoroensis only from B. diffusa. The present study confirms that Monosporascus spp. can colonize roots of T. portulacastrum and B. diffusa, and reveals that there is a high diversity of species. In the second work, a collection of 94 isolates of Macrophomina spp. obtained from roots of T. portulacastrum and B. diffusa were used, where they were characterized using molecular techniques and pathogenicity. Phylogenetic analysis of the tef-1α gene, amplified with the EF728F and EF986R primers, allowed the identification of 32 isolates as M. phaseolina and 62 isolates as M. pseudophaseolina. Results of the pathogenicity test performed on 'Gladial' melon seedlings revealed that both species are pathogenic to this cucurbitaceae, with M. phaseolina presenting a higher incidence and severity of the disease. This study represents the first report of M. pseudophaseolina in plants of T. portulacastrum and B. diffusa in Brazil
Keywords: Filogenia; Fungo; Patogenicidade; Taxonomia; Phylogeny; Fungus; Pathogenicity; Taxonomy; CIENCIAS AGRARIAS::AGRONOMIA::FITOTECNIA